Bone Microarchitecture in Obese Postmenopausal Chinese Women: The Chinese Vertebral Osteoporosis Study (ChiVOS) - Qi, Wenting; Jiang, Yan; Liu, Wei; Chi, Yue; Jiajue, Ruizhi; Pang, Qianqian; Wang, Ou; Li, Mei; Xing, Xiaoping; Yu, Wei; Xia, Weibo (Frontiers in Endocrinology, 2022)
Background Obesity is associated with improved bone mass and microarchitecture in Caucasian individuals, but evidence in obese Asian individuals is lacking. Objective To analyze the areal bone mineral density (aBMD) and bone microarchitecture in normal-weight, overweight, and obese postmenopausal Chinese women. Methods A total of 243 postmenopausal women from the Chinese Vertebral Osteoporosis Study (ChiVOS) were included and were divided into three groups (OB, obese group; OW, overweight group; NW, normal weight group) by BMI level. aBMD, trabecular bone score (TBS), and appendicular lean mass (ALM) were measured by dual‐energy X‐ray absorptiometry (DXA). Bone microarchitecture was measured by HR-pQCT at the distal radius and tibia. X-ray was performed to confirm vertebral fractures (VFs). Multiple linear regression was used to evaluate the correlations between bone parameters and ALM after adjusting for confounding variables. Results The prevalence of VFs and clinical fractures were similar among the groups. Participants in the OB group showed a lower level of osteocalcin with comparable levels of other bone turnover markers (BTMs). The aBMD at several skeletal sites was higher in the OB group than in the NW group after adjusting for age (p<0.01 for all comparisons). At the radius, the OB group had a higher Ct.Ar, Tb.vBMD, Tb.BV/TV, Tb.N, Tb.Th, and Ct.Th than the NW group after adjusting for covariates (p<0.05 for all). Differences of a similar magnitude were found at the distal tibia. There was a trend of decreasing trend in Tb.Sp, Tb.1/N/SD, and Ct.Po among groups at both sites. However, the bone microarchitecture did not differ between participants with severe obesity (BMI≥35.0kg/m2) and those with 30.0≤BMI＜35 kg/m2. Multiple linear regression revealed that the associations between ALM and most of the bone microarchitecture parameters at both sites were much stronger than the association between body weight and bone parameters. Conclusion We have observed significant improvements in aBMD, bone geometry, and bone microarchitecture in obese postmenopausal Chinese women. Except for a lower level of osteocalcin in the OB group, no significant differences in BTMs were found among the groups. Compared with body weight, ALM may explain greater variance in the improvement of bone microarchitecture parameters.